Study and Review of Helium Gas Turbine Technology for High-temperature Pre-cooler Gas - Sadaa, Suhayb Lateef (European Scientific Journal, ESJ, 2019)
The technology of pre-cooler system is the strongest means of air cooling and heat exchangers in the world. Heat exchangers that cool the incoming air are the biggest technical challenge At Mach 5 (5 times the speed of sound),To meet this challenge, REL (Reaction Engines Ltd) is a UK-based company , has developed the most powerful lightweight heat exchangers in the world -.The air enters the radiator to a compressor such as the jet engine, and it is pre-cooled from 1,000°C to minus 150°C, in 1/100th of a second, displacing 400 Mega-Watts of heat energy (equivalent to the power output of a typical gas-powered power station) yet weighs less than 1¼ tons . Equivalent to a small power plant, a very high rate in the world of aviation. As the temperature inside the engine will decrease significantly, this will help the engine to continue to work normally and thus increase its speed comfortably. The pre-cooled cooling device weighs about a ton, which is a group of thin tubes that contain helium(heliumcondensate) in their liquid form. These pipes are intertwined with each other in spiral form. This device absorbs heat and air cooled to 150 °C below zero before entering the engine. With rising fuel costs there is an initiative to conserve fuel during flight. The breakthrough achieved will allow heat exchangers to be used for a whole range of new applications.